Mulheres quilombolas e culturas do escrito: voz e letra na comunidade quilombola do Mato do Tição/MG - Maria Raquel Dias Sales Ferreira (2016)
This thesis aims to present the results of a research concerning the ways of participation at the writing cultures of a group of women who have different papers at their community and also different education experiences at Quilombo Mato Tição Community, located in Jaboticatubas in the Metropolitan Region Belo Horizonte (Minas Gerais). Although this community is established in the oral tradition, the presence of new social actors, built by the intensification of the school practices and by the new configurations of the quilombos legislations, contribute to intensify the dialogue with the government, NGOs, universities, social movements, among others and, consequently, the new uses of writing, different from those of their everyday practice. These practices define both the literacy process of these women as also the relation with oral and traditional practices performed especially by the older people. We analyze the orality performances, the ways to use the writing, the relationship between orality and literacy and its implications for social practices, and the establishment and the maintenance of a quilombo identity. This research is a result of an ethnography, in which we seek to identify the interactions of individuals with the writing and the oral practices operations. The new policy settings arising from the Constitution of 1988 and its aftermath implicated the quilombo recognition, that caused changes in ways of producing and of transmitting knowledge, and often, the ways in which social actors resignify its role in culture, identity and community cultural content. This process was permeate for relations with the written cultures, once the writing is connected and determines social and historical conditions, specific techniques and brought political, social and cultural impacts.